Suppression of phytopathogenic fungi using garlic, horsetail, and yarrow plant extracts - Saud Hamidović; Berina IMAMOVIĆ; Fejzo BAŠIĆ; Muamer BEZDROB; Nermin RAKITA; Blažo LALEVIĆ (Journal of Central European Agriculture)
Organic production is a system of sustainable agriculture based on a high respect for environmental principles through the rational use of natural resources, renewable energy sources, conservation of natural diversity, and environmental protection. Plant cultivation in organic production implies the application of preparations on a natural basis, which is most often used as a preventive measure without the application of agrochemicals. Therefore, the use of "domestic" natural pesticides is increasingly present. In this study, the antimicrobial effect of garlic (Allium sativum L.), horsetail (Equisetum arvense L.), and yarrow (Achillea millefolium L.) extract on the growth of phytopathogenic fungi of the genus Fusarium, Alternaria, and Aspergillus was tested. The potato dextrose agar was inoculated with the mycelia of fungi. The filter paper discs impregnated with 15 μL of plant extracts were placed onto agar. In the control sample, distilled water was used for the impregnation of paper discs. All experiments were performed in triplicate. Inhibition zone measurements were performed on the third day. The results showed that each of the mentioned plant extracts inhibited the growth of the phytopathogenic fungi. The lowest inhibition zone was observed using the garlic extract, while the highest inhibition zone was detected on the disc that was impregnated with yarrow extract. These results confirm the use of plant extracts in the suppression of phytopathogenic fungi.